Students’ Perception of SMAN 1 Grogol Kediri on the Application of Blended Learning In Teaching Reading - Rossi Dila Agustina; Lely Setyawati; Irwan Sulistyanto (Journal of English Development, 2023)
This study aims to (1) to find out how the application of Blended Learning at SMAN 1 Grogol in learning to read. (2) Describe the obstacles faced by students in the application of blended learning in learning to read at SMAN 1 Grogol Kediri. (3) To find out students' perceptions about the application of blended learning in learning to read at SMA Negeri 1 Grogol. The research method used is descriptive qualitative type. Qualitative research by using the approach of observation, interviews, questionnaires and documentation. The results showed that the application of Blended Learning at SMAN 1 Grogol Kediri was carried out using Rotation model. The application of Blended Learning in teaching reading at SMAN 1 Grogol Kediri uses the face-to-face lecture method. The platforms used by the English teacher at SMAN 1 Grogol Kediri during online learning are Google Classroom, WhatsApp Groups and Zoom. Students' Perceptions about the Application of Blended Learning in teaching reading at SMAN 1 Grogol Kediri most students have negative perceptions in online session.